One-Pot Copper-Catalyzed Three-Component Synthesis of Quinoxalines by Condensation and C−N Bond Formation - Yuan, Hua; Li, Kangning; Chen, Yongxin; Wang, Yu; Cui, Jiaojiao; Chen, Baohua (Synlett, 2013)
A novel way of synthesizing quinoxalines has been developed that involves condensation and C−N bond formation in a copper-catalyzed, one-pot, three-component reaction. The reaction was optimized when 2-iodoanilines (1.0 equiv), arylacetaldehydes (2.0 equiv), sodium azide (1.2 equiv), CuI (10 mol%), DMEDA (10 mol%), and K2CO3 (1.0 equiv) were reacted in DMSO at 80 °C for 20 hours. This approach was used to directly synthesize a variety of quinoxalines in moderate to good yields.
Keywords: quinoxalines; arylacetaldehydes; sodium azide; three-component reaction